Antimicrobial and mechanism of antagonistic activity of Bacillus sp. A2 against pathogenic fungus and bacteria: The implication on honey's regulatory mechanism on host's microbiota. Issue 9 (20th July 2020) - Jia, Lina; Kosgey, Janet Cheruiyot; Wang, Jielin; Yang, Jianxun; Nyamao, Rose Magoma; Zhao, Yi; Teng, Xue; Gao, Lei; Wabo, MartinTherese Cheteu; Vasilyeva, Natalia V.; Fang, Yong; Zhang, Fengmin
Abstract: Honey is thought to act against microbes and regulates microbiota balance, and this is mainly attributed to the enzymatic production of hydrogen peroxide, high osmolarity, and nonperoxidase factors, for example, lysozyme and botanical sources of nectar, while the effect of honey's probiotic is recently considered. The study of honey as source of beneficial microbes is understudied. The purpose of this study was to screen for the beneficial microorganisms in honey with antagonistic property against important pathogens and the mechanism of antimicrobial activity and thus play a beneficial role as probiotics. The results showed that one out of the fourteen bacterial isolates had antimicrobial activity and was identified as Bacillus Sp. A2 by 16S rRNA sequence and morphology. Antimicrobial activity of the isolate against C. albicans, E. coli, and S. aureus was confirmed by Agar well diffusion and liquid coculture assays, and the propagation of those microbes was significantly inhibited after treatment with the isolate Bacillus sp. A2 ( p < .05) in comparison with untreated negative control and positive control (fluconazole, chloramphenicol, L. plantarum ). The morphological changes including the distorted shape with indentations and leakages ( SEM ), damaged cell membrane, and cell wall with the disintegration and attachment of the Bacillus sp. A2 (TEM) in treated C. albicans were observed. Meanwhile, reactive oxygen species accumulation and decreased mitochondrial membrane potential were detected in treated C. albicans . These results revealed that the isolate Bacillus sp. A2 from honey has significant antimicrobial activity ( p < .05) against C. albicans in comparison with untreated negative control and positive control L. plantarum, which depends on the accumulation of reactive oxygen species, mitochondrial damage, and the cell apoptosis. We concluded that the Bacillus sp. A2 possess the antimicrobial property, which may contribute to regulation of host's microbiota as a beneficial microbe or probiotic. Abstract : Antimicrobial activity of B. amyloliquefaciens A2 from honey against C. albicans, C. glabrata, E. coli, and S. aureus in vitro. B. amyloliquefaciens A2 from honey induce ROS accumulation, mitochondrial damage, and cell apoptosis in C. albicans . It is implicated that the beneficial microbe or probiotics in honey is contributed to the honey's antimicrobial activity and regulation of host's microbiota balance.